2022
DOI: 10.1097/prs.0000000000009645
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Botulinum Toxin Type A in the Treatment of Benign Parotid Hypertrophy: a Prospective, Single-arm Clinical Trial

Abstract: Background: Benign parotid hypertrophy makes the earlobe area appear swollen and weakens the lateral facial contour and aesthetics. Efficacious treatment for benign parotid hypertrophy is not available. The authors evaluated the efficacy and safety of botulinum toxin type A for benign parotid hypertrophy treatment. Methods: Thirty-six participants with benign parotid hypertrophy were enrolled and treated with botulinum toxin type A injection. After 6 months of follow-up, changes in the thickness and length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The parotid gland can be clearly visualized when enlarged at the medial side of the tragus area. 17 Doppler ultrasound can be used during the thread lifting as it allows visualizing the cannula during the process. However, it is difficult to use because thread insertion requires using both hands, thus limiting the availability of the hands to hold the ultrasound probe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The parotid gland can be clearly visualized when enlarged at the medial side of the tragus area. 17 Doppler ultrasound can be used during the thread lifting as it allows visualizing the cannula during the process. However, it is difficult to use because thread insertion requires using both hands, thus limiting the availability of the hands to hold the ultrasound probe.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound helps detect the exact location of the parotid gland in individual patients. The parotid gland can be clearly visualized when enlarged at the medial side of the tragus area 17 . However, it usually cannot be detected clearly, especially in the cheek area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 A prospective study on adults with benign parotid hypertrophy found that repetitive injections could lessen gland thickness at 3 and 6 months, with minimal side effects. 11 In the article by Jeong et al, the single BTX-A injection resulted in volume reduction at 2 weeks with a rebound effect at 3 months, which is atypical based on prior literature. 1 No explanation for this phenomenon is provided, but presumably, given that these facial trauma patients did not have a prior diagnosis of parotid hypertrophy and they may have had traumatic facial swelling preoperatively, the effect of BTX-A may have been confounded.…”
mentioning
confidence: 95%
“…10 A prospective study on adults with benign parotid hypertrophy found that repetitive injections could lessen gland thickness at 3 and 6 months, with minimal side effects. 11…”
mentioning
confidence: 99%